2007
DOI: 10.1002/pmic.200600784
|View full text |Cite
|
Sign up to set email alerts
|

myProMS, a web server for management and validation of mass spectrometry‐based proteomic data

Abstract: Curation and interpretation of protein databank-search results by human experts are key aspects of MS-based proteomic data acquisition. These tasks are often overlooked due to the vast amount of data to inspect. We have developed myProMS, a web server designed to ease search results validation and interpretation by improving data organization, mining and sharing between MS specialists and biologists during MS-based collaborative projects. A demo is accessible at http://bioinfo.curie.fr/myproms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
143
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 10 publications
0
143
0
Order By: Relevance
“…Peptide false positive identification probability was <5%. All identified proteins from several injections were compared using the MyproMS data parser [59]. Proteins were confidently identified with at least 2 different peptides with a score of identification ≥20.…”
Section: Methodsmentioning
confidence: 99%
“…Peptide false positive identification probability was <5%. All identified proteins from several injections were compared using the MyproMS data parser [59]. Proteins were confidently identified with at least 2 different peptides with a score of identification ≥20.…”
Section: Methodsmentioning
confidence: 99%
“…A peptide mass tolerance of 7 ppm and a fragment mass tolerance of 0.5 Da were allowed for identification. Peptide validation and peptide counting were performed using the MyProMS version 2.3 Web server (Poullet et al, 2007), to obtain a false discovery rate Ͻ1%. Only proteins identified with two or more peptides by MS/MS were considered as potential SERT partners.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that protein kinase C (PKC) activation inhibits 5-HT transport activity of SERT in both recombinant (HEK-293 cells) and native (platelets, synaptosomes) systems and that this effect is paralleled by an increase in SERT phosphorylation (Qian et al, 1997;Ramamoorthy et al, 1998;Jayanthi et al, 2005;. We thus wondered whether CaN phosphatase activity could affect PKC-mediated SERT regulation.…”
Section: Calcineurin Prevents Sert Phosphorylation and Inhibition Of mentioning
confidence: 99%
“…A statistical evaluation of the validation efficiency of Peptizer compared with other tools was omitted here because determination of the variance specific to the tools was impractical. However, compared with other semimanual postprocessing applications such as CHOMPER (18), DTASelect (19), or myProMS (20), Peptizer stands out by being fully configurable. Although these existing tools may allow the configuration of a fixed set of criteria, Peptizer has no fixed set of criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the so-called "single hit wonders", which often populate the majority of identified peptides or proteins in gel-free proteomics, should not be simply discarded but must be treated intelligently as they potentially contain valuable biological information (16,17). The manual validation required to assure the reliability of the biological conclusions drawn from such peptide identifications can be performed by using the visualization tools included with the search engine or by specialized applications such as CHOMPER (18), DTASelect (19), or myProMS (20). These tools present a specific set of details on a peptide identification and its associated spectrum for user validation.…”
mentioning
confidence: 99%